2019
DOI: 10.1007/s00268-019-04987-z
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoparathyroidism After Total Thyroidectomy: Importance of the Intraoperative Management of the Parathyroid Glands

Abstract: Background Total thyroidectomy is the most common surgical procedure for the treatment of thyroid diseases. Postoperative hypocalcemia/hypoparathyroidism is the most frequent complication after total thyroidectomy. The aim of this study was to evaluate the rate of postoperative hypocalcemia and permanent hypoparathyroidism after total thyroidectomy in order to identify potential risk factors and to evaluate the impact of parathyroid autotransplantation. Patients and MethodsWe performed a retrospective analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 36 publications
(58 reference statements)
1
43
2
3
Order By: Relevance
“…Patients with three or more ISPGs scarcely underwent permanent hypoparathyroidism, nor did patients with 3 or more APGs. 3 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with three or more ISPGs scarcely underwent permanent hypoparathyroidism, nor did patients with 3 or more APGs. 3 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Among the complications of thyroid surgery, postoperative hypoparathyroidism was the most common. 3,4 The incidence of transient hypoparathyroidism ranged from 10.8% to 64.4%, and the incidence of permanent hypoparathyroidism varied from 0 to 31.1% across different researches. [5][6][7][8] Hypoparathyroidism was the consequence of the reduction of the functional parathyroid parenchyma for mechanical or thermal trauma, devascularization, and inadvertent resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ponce de Leon-Ballesteros and his colleagues discovered that 3 or more PGs should be preserved in site to decrease the risk of permanent hypoparathyroidism. [ 30 ] And de Jong et al and Lorente-Poch et al believed that the more the PGs were preserved in site, the lower the incidence of permanent hypoparathyroidism was. [ 31 , 32 ] However, several other studies suggested that autotransplantation of 2 or more PGs could prevent permanent hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia following operation for differentiated thyroid carcinoma (DTC) remains one of the most common postoperative complications, it may prolong hospitalization and require medical intervention (1). A series of studies have reported incidences of 20-80% (2,3).…”
Section: Introductionmentioning
confidence: 99%